Diabetes-related skin problems and proper cosmetic care as a simple and affordable way to correct them: A review - Andrey F. Verbovoy; Yulia A. Dolgikh (ZAO "Consilium Medicum", 2024)
Diabetes mellitus (DM) is a non-communicable epidemic. The number of people with this pathology is growing every year. DM leads to a decrease in quality and life expectancy due to vascular complications. However, the manifestations of diabetes are varied, including possible skin manifestations, which often receive insufficient attention. This article analyzes and summarizes current knowledge about dermatological complications in patients with DM, with an emphasis on the pathogenetic mechanisms underlying these problems. This article focuses on xerosis, intertrigo and disorders of the skin's protective mechanisms during the development of diabetic foot. The article is aimed at developing practical recommendations for endocrinologists on skin care in patients with diabetes, in order to improve their quality of life and prevent complications. The need to expand patient education on skin care in Diabetes Schools is also discussed.